2018
DOI: 10.1111/pce.13189
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide signatures of flowering adaptation to climate temperature: Regional analyses in a highly diverse native range of Arabidopsis thaliana

Abstract: Current global change is fueling an interest to understand the genetic and molecular mechanisms of plant adaptation to climate. In particular, altered flowering time is a common strategy for escape from unfavourable climate temperature. In order to determine the genomic bases underlying flowering time adaptation to this climatic factor, we have systematically analysed a collection of 174 highly diverse Arabidopsis thaliana accessions from the Iberian Peninsula. Analyses of 1.88 million single nucleotide polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
80
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(83 citation statements)
references
References 79 publications
(152 reference statements)
3
80
0
Order By: Relevance
“…Dispersal barriers have important consequences for population dynamics, allelic and species distributions, and community compositions (Caplat et al, ). Tabas‐Madrid et al () directly confirmed this effect by reporting the presence of four distinct genetic groups around Iberia and even provide evidence and speculation about their life history.…”
mentioning
confidence: 87%
See 4 more Smart Citations
“…Dispersal barriers have important consequences for population dynamics, allelic and species distributions, and community compositions (Caplat et al, ). Tabas‐Madrid et al () directly confirmed this effect by reporting the presence of four distinct genetic groups around Iberia and even provide evidence and speculation about their life history.…”
mentioning
confidence: 87%
“…The study by Tabas‐Madrid et al () also illustrates the importance of studying plants at the regional scale and taking environmental variables into account when breeding crops with genomics‐based strategies. All life adapts to selective pressures imposed on it by their environment through natural selection (Figure ).…”
mentioning
confidence: 99%
See 3 more Smart Citations